EXAMINATION OF PRE-SERVICE TEACHERS' ANXIETY LEVELS ABOUT TEACHING PROFESSION - Karakaya, Ferhat; Avgın, Sakine Serap; Gömlek, Elif; Balık, Merve (International Online Journal of Education and Teaching, 2017)
In this research, it was aimed to determine the levels of occupational anxiety of pre-service teachers' who read science and primary school teacher programs according to various variables. The research was carried out by Köklükaya and Yıldırım (2016) and the validity and reliability analyzes were carried out. Anxiety Scale for Teaching Profession (ASTP) was used. The research was carried out with 266 prospective teachers who were educated at Kahramanmaras Sütcü Imam University in the academic year of 2015-2016. Independent t test, one way analysis of variance (anova), Mann-Whitney U test, Kruskal-Wallis analysis and Tukey significance test were used to determine the statistical significance of the obtained data in the research using relational screening model. According to research findings, it was determined that there was no significant difference (p <.05) in the level of vocational anxiety among the teacher candidates according to the degree of willingness to choose the department, grade level and academic achievement score. According to the gender variable, there was no significant difference in the pre-service teachers' who read in the department of primary school teachers', and it was found that the science teachers' professional anxiety levels had a significant difference according to the gender variable.